SISTEM PEMIDANAAN EDUKATIF OLEH HAKIM TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM - Indra Cosmas Silalahi (2021)
This research was conducted to complete the Thesis, as one of the requirements for obtaining a Master of Law degree. This study discusses the educative punishment system for children in conflict with the law as a form of actualization of the rights for children who have committed a criminal act, it will discuss various problems related to obstacles and solutions to overcome the best obstacles for children who are have problems with the law. Based on this description, the background of the problem of implementing the educative punishment system carried out by judges to children, it will be formulated to identify problems regarding the obstacles that hinder the application of the educative punishment system by judges to children who have problems with the law and implementation of the educative punishment system by judges to children have problems with the law. This type of research on the educative punishment system by judges for children who have problems with the law is a type of research that is included in normative legal research, namely research that uses statutory regulations as a reference. This research can also be said to be a library research because this research uses legal materials derived from the collection of a literature study. In the application of the educative punishment system by judges to children who have problems with the law, there are still several obstacles, such as in the imposition of criminal sanctions decisions without regard to the background of the child, lack of facilities and infrastructure.